2020
DOI: 10.2196/19436
|View full text |Cite
|
Sign up to set email alerts
|

Use of Decision Support Tools to Empower Pregnant Women: Systematic Review

Abstract: Background Women face many health-related decisions during pregnancy. Digitalization, new technology, and a greater focus on empowering patients have driven the development of patient-centered decision support tools. Objective This systematic review provides an overview of studies investigating the effect of patient-centered decision support tools for pregnant women. Methods We searched 5 online databases, M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Earlier studies have shown that the majority of the pregnant population owns a smartphone and over 50% use apps related to pregnancy [ 36 ]. Studies that have investigated the use of health-related apps have shown that the apps could improve the knowledge levels of pregnant women and the apps were perceived as tools during pregnancy [ 7 , 24 ]. Except for user satisfaction, our results were not consistent with those from previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have shown that the majority of the pregnant population owns a smartphone and over 50% use apps related to pregnancy [ 36 ]. Studies that have investigated the use of health-related apps have shown that the apps could improve the knowledge levels of pregnant women and the apps were perceived as tools during pregnancy [ 7 , 24 ]. Except for user satisfaction, our results were not consistent with those from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our review from 2020, consistent with previous studies [ 48 ], demonstrated that decision support tools could potentially provide benefit to pregnant women. However, the tools were mainly useful when relevant information was assembled into one digital tool and when the woman could share her recordings with her health care provider [ 7 ]. Based on the results of this study, future research should focus on how to design trials to determine the effect of digital tools on the pregnancy outcomes that are most important to pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medication reviews provided by pharmacists have showed increased knowledge and compliance, and a more positive attitude toward medication use [18]. Earlier studies have demonstrated that pharmaceutical care improves health outcomes, con dence in decision-making, knowledge, and communication and is cost-effective as well [19,20]. We have previously found that a pharmacist intervention for pregnant women in the rst trimester was feasible and highly appreciated by the women themselves [21,22].…”
Section: Introductionmentioning
confidence: 99%